2006
DOI: 10.1007/s10571-006-9021-4
|View full text |Cite
|
Sign up to set email alerts
|

Norlaudanosoline and Nicotine Increase Endogenous Ganglionic Morphine Levels: Nicotine Addiction

Abstract: 1. Given the presence of morphine, its metabolites and precursors, e.g., norlaudanosoline, in mammalian and invertebrate tissues, it became important to determine if exposing normal excised ganglia to norlaudanosoline would result in increasing endogenous morphine levels. 2. Mytilus edulis pedal ganglia contain 2.2 +/- 0.41 ng/g wet weight morphine as determined by high pressure liquid chromatography coupled to electrochemical detection and radioimmunoassay. 3. Incubation of M. edulis pedal ganglia with norlau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…In sum, previous work from our laboratory has demonstrated that multiple substances of abuse have the ability to enhance endogenous morphine processes at a common step, e.g., release from cellular stores, in invertebrate and human tissues [23, 24 28, 30]. In the present report we further demonstrate that chronic exposure of neural tissues to ethanol induces a time dependent increase in both endogenous morphine and DA levels.…”
Section: Introductionsupporting
confidence: 78%
“…In sum, previous work from our laboratory has demonstrated that multiple substances of abuse have the ability to enhance endogenous morphine processes at a common step, e.g., release from cellular stores, in invertebrate and human tissues [23, 24 28, 30]. In the present report we further demonstrate that chronic exposure of neural tissues to ethanol induces a time dependent increase in both endogenous morphine and DA levels.…”
Section: Introductionsupporting
confidence: 78%
“…It appears that after more than 30 years of research into an animal's ability to make morphine the empirical evidence is now overwhelming. Recent reports have also demonstrated that major substances of abuse, i.e., nicotine, alcohol, and cocaine, appear to work via altering endogenous morphinergic signaling in a common manner, i.e., inducing morphine release 25 , 88–93 . Furthermore, endogenous morphine participates in physiological processes transcending pain, making it an important chemical messenger.…”
Section: Resultsmentioning
confidence: 99%
“…Nicotine induced c-fos within CRF and Enk, but not DYN cells within the PVN (698). Norlaudanosoline and nicotine increase endogenous invertebrate ganglionic morphine (1328). Chronic swim stress increased nicotine's ability to increase plasma ACTH and BEND, but not corticosterone, whereas stress itself increased plasma corticosterone, but not ACTH or BEND (703).…”
Section: F Opiates and Other Drug Abuse Classesmentioning
confidence: 90%